Management and diagnosis of tuberculosis in solid organ transplant candidates and recipients: Expert survey and updated review,. (May 2018) - Pennington, Kelly M.; Kennedy, Cassie C.; Chandra, Subhash; Lauzardo, Michael; Brito, Maximo O.; Griffith, David E.; Seaworth, Barbara J.; Escalante, Patricio
Abstract: Background : Optimal screening and management of latent tuberculosis infection (LTBI) and active tuberculosis (TB) in solid organ transplant (SOT) candidates and recipients is necessary to prevent morbidity and mortality. Methods : We conducted a cross-sectional survey of TB and transplant experts across the United States reviewing the clinical practice preferences on key management issues related to LTBI and TB in SOT candidates and recipients. Results : Thirty TB and 13 SOT experts were surveyed (response rate = 53.8%). Both groups agreed that tuberculin skin test (TST) and chest x-ray screening in SOT candidates was useful (78.6% and 84.6%, respectively). TST after SOT was not useful for most transplant experts and TB experts (0% vs. 32.1%, respectively), but both groups were split on usefulness of interferon gamma release assays (IGRA) in SOT recipients (42.9% TB experts vs. 46.2% SOT experts). Most experts recommend LTBI treatment prior to SOT if close monitoring is assured (82.1% TB experts vs. 76.9% transplant experts). LTBI treatment with isoniazid was preferred for patients on calcineurin inhibitors. Evaluation for suspected TB in SOT recipients varied, but most TB experts favored sputum testing (88.9%) whereas most transplant experts favored bronchoscopic testing (69.2%). Preferred TB treatment regimens in SOT recipients were similar to regimens recommended for immunocompetent patients. Conclusions : Most TB and transplant experts recommend evaluation and treatment for LTBI in SOT candidates. Liver transplant candidates, however, should only be treated if close monitoring can be assured and after consulting with a hepatologist. Practice preferences varied regarding the initial diagnostic approach for suspected TB in SOT recipients; however, most experts agreed that SOT recipients should receive similar treatments as immunocompetent patients.